BRD4 inhibitors block telomere elongation. Issue 14 (30th June 2017) - Wang, Steven; Pike, Alexandra M.; Lee, Stella S.; Strong, Margaret A.; Connelly, Carla J.; Greider, Carol W.
Abstract: Cancer cells maintain telomere length equilibrium to avoid senescence and apoptosis induced by short telomeres, which trigger the DNA damage response. Limiting the potential for telomere maintenance in cancer cells has been long been proposed as a therapeutic target. Using an unbiased shRNA screen targeting known kinases, we identified bromodomain-containing protein 4 (BRD4) as a telomere length regulator. Four independent BRD4 inhibitors blocked telomere elongation, in a dose-dependent manner, in mouse cells overexpressing telomerase. Long-term treatment with BRD4 inhibitors caused telomere shortening in both mouse and human cells, suggesting BRD4 plays a role in telomere maintenance in vivo . Telomerase enzymatic activity was not directly affected by BRD4 inhibition. BRD4 is in clinical trials for a number of cancers, but its effects on telomere maintenance have not been previously investigated.